2021
DOI: 10.1007/s11356-021-13185-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urbanisation and a wastewater treatment plant on microplastic densities along a subtropical river system

Abstract: Global freshwaters are increasingly threatened by pollutants emanating from human activities around watersheds. Microplastic pollution is an increasing problem for rivers worldwide, potentially threatening ecological integrity, ecosystem services and human health. We present quantifications and characterisations of sediment microplastic pollution in a subtropical river system in southern Africa, and relate distributions to wastewater treatment works, abiotic variables and urban environments. We additionally ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 42 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Plastic and microplastic research in Africa remains limited compared to other continents, but recent efforts to highlight microplastic pollution in Africa has been made (Naidoo et al, 2015;Nel and Froneman, 2015;Biginagwa et al, 2016;Lourenco et al, 2017;Nel at al., 2017;Nel et al, 2018;Akindele et al, 2019;Dalu et al, 2019;Mayoma et al, 2019;Toumi et al, 2019;Weideman et al, 2019;Weideman et al, 2020;Dahms et al, 2020;Alimi et al, 2021;Dalu et al, 2021;Deme et al, 2022;Masiá et al, 2022). In South Africa, research has been conducted on microplastics in the Vaal River system, determining microplastic concentrations in water, sediment, and the ability for longdistance transfer of microplastics (Weideman et al, 2019;Weideman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Plastic and microplastic research in Africa remains limited compared to other continents, but recent efforts to highlight microplastic pollution in Africa has been made (Naidoo et al, 2015;Nel and Froneman, 2015;Biginagwa et al, 2016;Lourenco et al, 2017;Nel at al., 2017;Nel et al, 2018;Akindele et al, 2019;Dalu et al, 2019;Mayoma et al, 2019;Toumi et al, 2019;Weideman et al, 2019;Weideman et al, 2020;Dahms et al, 2020;Alimi et al, 2021;Dalu et al, 2021;Deme et al, 2022;Masiá et al, 2022). In South Africa, research has been conducted on microplastics in the Vaal River system, determining microplastic concentrations in water, sediment, and the ability for longdistance transfer of microplastics (Weideman et al, 2019;Weideman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additional findings suggest that increased urbanization and wastewater treatment plants serve as primary sources of microplastic pollution within freshwater systems (Schmidt et al, 2018;Talbot and Heejun, 2022). An investigation of a subtropical river in southern Africa, however, did not find a clear spatial distribution pattern of microplastics relative to a wastewater treatment plant (Dalu et al, 2021). A recent field sampling study of an urban creek in Illinois concluded that concentrations of microplastics in urban streams may be orders of magnitude greater than in larger rivers (Noseworthy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, rivers are a major pathway of microplastics to the marine environment (Faris and Hart 1994 ; Allsopp et al 2006 ; Guerranti et al 2017 ; Lebreton et al 2017 ; Schmidt et al 2017 ; Li et al 2020 ) due to human activities, such as industry (Karlsson et al 2015 ), agriculture (Corradini et al 2019 ; GESAMP 2013 ; Huang et al 2021 ) or wastewater treatment plants (Kay et al 2018 ; Conley et al 2019 ; Dalu et al 2021 ). It has been estimated that between 1.15 and 2.41 million tons of plastic waste enter the ocean each year from rivers (Lebreton et al 2017 ), with 20 rivers (15 from Asia, 3 from Africa and 2 from South America) responsible of about 67% of the total world pollution.…”
Section: Introductionmentioning
confidence: 99%